Long-term effects of enhanced external counterpulsation in the management of patients with coronary artery disease complicated by heart failure: data from the EXCEL study - A. S. Lishuta; O. A. Slepova; N. S. Nikolaeva; E. V. Privalova; Yu. N. Belenkov (Российский кардиологический журнал, 2024)
Aim. To study the long-term effect of complex therapy with enhanced external counterpulsation (EECP) on exercise tolerance, quality of life, and systolic cardiac function in patients with stable coronary artery disease (CAD) complicated by heart failure (HF).Material and methods. Open randomized study EXCEL (NCT05913778) included 118 patients with verified stable CAD complicated by NYHA class II-III HF with reduced or mildly reduced ejection fraction (EF). The patients were randomized into group 1 (n=59) who received optimal therapy and EECP (35 hours, 2 courses per year) or group 2 (n=59), who recived optimal drug therapy and EECP (35 hours, 1 course per year). All patients underwent a 6-minute walk test (6MWT) at baseline, 12, 24 and 36 months, the assessment of clinical status, Minnesota Living with Heart Failure Questionnaire (MLHFQ), N-terminal pro-brain natriuretic peptide (NTproBNP) levels, LVEF and clinical outcomes.Results. In both groups, we revealed an improvement of HF class (average HF class after 36 months decreased in the 1st group from 2,40 to 1,86 (p<0,001), and in the 2nd group from 2,37 to 2,17 (p<0,001)) and clinical status of patients. A significant increase in 6MWT distance after 24 months was revealed in both groups — in group 1 by 59,4% (95% confidence interval (CI) 36,9-76,8), and in group 2 — by 34,3% (95% CI 26,7-40,1). The proportions of patients with an increase in 6MWD distance >20% in groups 1 and 2 after 36 months were 100% (n=59) and 79,7% (n=47) (p<0,001), respectively. There was a significant decrease in the MLHFQ score after 36 months in the 1st group by 43,8% (95% CI 40,5-47,1), and in the 2nd group by 30,0% (95% CI 26,4-33,6), NT-proBNP decrease, as well as an increase in LVEF. There were no deaths in group 1, while in group 2, mortality was 3,4%.Conclusion. A 36-month follow-up of patients with CAD complicated by HF receiving EECP revealed stable improvements in exercise tolerance, quality of life, systolic cardiac function, more pronounced in the group with 2 courses of EECP per year, as well as a decrease in the incidence of adverse outcomes.